Deteksi Dini Risiko Malnutrisi melalui Mini Nutritional Assessment dan Hipertensi pada Perempuan Pra-Lansia dan Lansia - Rayanti, Rosiana Eva; Permatasari, Gracia; Andanti, Maria Fransisca (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
This community service program aims to conduct early detection of malnutrition and hypertension risks in pre-elderly and older adult women using the Mini Nutritional Assessment (MNA) and blood pressure screening. The activity was conducted with 44 participants from the community, comprising 63.6% who were aged 30–59 years and 36.4% who were aged 60–80 years. The results showed double nutritional problems, with 22.7% of participants being obese and 11.3% in the thin category. Although 50% of participants had a body mass index ≥23, the quality of protein consumption was still limited, with 38.6% only meeting the 0–1 indicator of daily protein intake. Blood pressure screening identified 31.8% in the pre-hypertension phase, 27.3% with stage 1 hypertension, and 22.7% with stage 2 hypertension. The MNA found that 31.8% of participants were at risk of malnutrition, despite 79.5% perceiving their nutritional status to be good. These findings indicate a gap between health perceptions and objective conditions, as well as a significant risk of chronic disease in the pre-elderly group. Nutritional education interventions, increased protein consumption, weight control, and regular blood pressure monitoring are recommended to prevent the development of degenerative diseases. This program highlights the importance of comprehensive community-based screening as a promotive and preventive measure in enhancing the health of older women.